Estudo teórico da interação de derivados 1,4-diidropiridina com nanotubos de carbono singlewall - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
In recent decades since its discovery in 1991, because their electronic, mechanical and structural properties as well as its nanometer size the carbon nanotubes have been the subject of studies for many nanotechnologies applications ranging from electronics in nanocomposite generation and storage to biomedical energy, such as biosensors and drug delivery systems. 1,4-dihydropyridines derivatives obtained via Hantzsch reaction multicomponent are drugs with biological potential application as anti-hypertensive, anti-tumor, anti-HIV and blockers of calcium channels. The use of encapsulated drugs or nanostructures coupled to assist in the reduction of side effects, increased solubility and the body so that the drug is delivered to specific sites of action. In this work an initial theoretical study of carbon nanotube pure singlewall in armchair and zigzag conformations with 5 levels, and with 40 and 48 atoms per level interacting with 1,4-dihydropyridines derivatives 5 was carried out. Then, performed a theoretical study of their functionalization of nanotubes amide and carboxylic acid and subsequent interaction with groups derived. To perform the calculations of energy loads, HOMO-LUMO was used quantum semi-empirical (MOPAC-PM7) methods. There was only physical interaction between pure and functionalized nanotubes and derivatives demonstrated by small variations of energy, great distances and no significant changes in the HOMO-LUMO orbitals. Armchair nanotubes were more stable energetically, but the interactions were stronger with the zigzag nanotubes. There was more interaction with derivatives on the outside of the nanotube, justified by the reactivity on the tube walls due to its curvature. Pure nanotubes showed gap semiconductor and after functionalization increased the gap insulating characteristics. Physical interactions do not alter the properties of structures, and any stimulus can obtain the isolated structures are important for the development of a drug delivery system as possible application for the development of working characteristics.
Keywords: Nanotubo de carbono; 1,4-Diidropiridinas; Funcionalização; Carbon nanotube; 1,4-Dihydropyridines; Functionalization; CIENCIAS EXATAS E DA TERRA::QUIMICA